2017
DOI: 10.1038/s41598-017-17999-3
|View full text |Cite|
|
Sign up to set email alerts
|

Comparative profiling of cortical gene expression in Alzheimer’s disease patients and mouse models demonstrates a link between amyloidosis and neuroinflammation

Abstract: Alzheimer’s disease (AD) is the most common form of dementia, characterized by accumulation of amyloid β (Aβ) and neurofibrillary tangles. Oxidative stress and inflammation are considered to play an important role in the development and progression of AD. However, the extent to which these events contribute to the Aβ pathologies remains unclear. We performed inter-species comparative gene expression profiling between AD patient brains and the App NL-G-F/NL-G-F and 3xTg-AD-H mouse models. Genes commonly altered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
125
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 149 publications
(138 citation statements)
references
References 59 publications
12
125
0
1
Order By: Relevance
“…Our bulk brain analysis of microglia and astrocyte genes is consistent with the reported APP KI transcriptomic data (53). Upon examination of cell type-specific changes, we noted that most of the observed cellular changes occur in microglia and astrocytes, with little to none occurring in vascular endothelia or oligodendrocytes.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our bulk brain analysis of microglia and astrocyte genes is consistent with the reported APP KI transcriptomic data (53). Upon examination of cell type-specific changes, we noted that most of the observed cellular changes occur in microglia and astrocytes, with little to none occurring in vascular endothelia or oligodendrocytes.…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with reports using other AD models (51), Apoe is upregulated in both microglia and astrocytes of APP KI mice and such an increase has been proposed to serve as a clearance mechanism (52). Our bulk brain data are also consistent with recently published bulk transcriptomic data in the APP KI model showing increases in genes generally thought to be microglial (including Cst7, Clec7a, Lpl, Hexb, Spp1, Trem2, Tyrobp, and C3ar1) and astrocytic (including Gfap, Serpina3, and Osmr) ( Figure 5, A-C) (53). In agreement with previous bulk brain data from AD mouse models (53-55), we found that genes of the complement pathway were also significantly upregulated (C1qa, C3ar, C4b, Itgam, and Itgb2) at the bulk tissue level.…”
Section: Inflammatory Profile Of Cobra-isolated Cells Following Peripsupporting
confidence: 92%
See 1 more Smart Citation
“…Recently, it was reported that TREM2, as well as CD36 and the receptor for advanced glycation end‐products, work as Aβ sensor molecules and activate microglia . A consistent and elevated expression of TREM2 was described in App NL‐G‐F KI mice . Activated microglia also produce the pro‐inflammatory cytokines CCL3/MIP‐1α and interleukin (IL)‐6, the latter being a key component of the senescence‐associated secretory phenotype, which might provide a pathophysiological connection between cellular/tissue senescence and age‐related chronic diseases in the brain, including AD.…”
Section: Neuroinflammatory Glial Responses (Relevance To the Brain's mentioning
confidence: 99%
“…reported amyloidosis‐dependent transcriptomic profiles in 3xTg AD mice and App NL‐G‐F KI mice . In contrast to 3xTg AD mice, App NL‐G‐F KI mice express genes in common with AD patients, such as neuroinflammation‐related genes ( C4a/C4b , Cd74 , Ctss , Gfap , Nfe212 , Phyhd1 , S100b , Tf , Tgfbr2 and Vim ) and AD risk factor genes ( Abi3 , Apoe , Bin2 , Cd33 , Ctsc , Dock2 , Fcer1g , Frmd6 , Hck , Inpp5D , Ly86 , Plcg2 , Trem2 and Tyrobp ) . Thus, App KI mice might overcome some of the previous limitations associated with APP overexpression‐based mouse models, and could thus serve as a useful research tool for further investigations.…”
Section: Animal Models For Ad and Neuroinflammationmentioning
confidence: 99%